METHODS FOR DEVELOPING STUDENT’S COMPARATIVE AND CRITICAL THINKING SKILLS THROUGH TEACHING FOREIGN DRAMATIC WORKS (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2026)
This article examines the theoretical and methodological foundations of teaching dramatic works from world literature. It also analyzes tasks related to the purposeful and systematic integration of students’ classroom activities, independent learning, and extracurricular work.